Elevated mean arterial pressure and risk of impaired fasting glucose: a multicenter cohort study revealing age and sex interactions - Lin, Yuye; Zou, Junzhong; Hong, Miaoling; Huang, Xudong; Wu, Juan (Frontiers in Endocrinology, 2025)
BackgroundEvidence connecting mean arterial pressure (MAP) with impaired fasting glucose (IFG) was currently insufficient. The purpose of our research was to investigate how age and sex individually affect the relationship between MAP and the onset of IFG.MethodsOur study was a retrospective cohort analysis involving 184,291 participants from a multicenter health examination in China. The relationship between MAP and the onset of IFG was evaluated using Cox regression analysis. To further investigate the relationship, smooth curve fitting was applied to evaluate the dose-response association, while threshold effect analysis was performed to identify potential inflection points in MAP. Additionally, interaction effect analysis was conducted to examine whether age and sex modified the association between MAP and IFG risk.ResultsThe overall incidence of IFG was 11.28%. After multivariate adjustment, a significant positive association was observed between MAP and IFG risk (Hazard Ratio: 1.14, 95% Confidence Interval: 1.12–1.16, P < 0.001). Multivariate smooth splines analysis revealed a nonlinear relationship (P for nonlinearity < 0.05), with the curve slope decreasing as MAP exceeded 103.23 mmHg. Significant interaction effects between MAP and age or sex on IFG risk were also identified (P < 0.05).ConclusionsOur study revealed new insights into how MAP and IFG development were related, highlighting the influence of age and sex. These results stressed the need to consider MAP, age, and sex in IFG prevention, especially in high-MAP groups. Further investigation into the biological and behavioral mechanisms underlying these age- and sex-dependent relationships is warranted to inform personalized approaches for diabetes prevention.